Social sources of disparities in health and health care and linkages to policy, population concerns, and providers of care - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2009)
"Volume 27, Research in the Sociology of Health Care" deals with Social Sources of Disparities in Health and Health Care. The first section, Disparities in Health and Health Care: Basic Perspectives, reviews basic material on the topic. The second section on Racial and Ethnic Factors in Disparities in Health and Health Care Utilization includes five articles, three focused on racial and ethnic factors in disparities and two on those factors and other social factors such as SES. The next section focuses on Income, SES, and Cultural Capital in Disparities in Health and Health Care Delivery and includes an article that focuses on the role of education, one on the impact of childhood poverty on later life health and one on the role of cultural capital in health outcomes. The fourth section includes two papers on Providers, Facilities and Health Disparities. The last section, Part 5, deals with Locally Oriented Studies in Health Disparities and includes three papers looking at community approaches for eliminating health disparities, the effects of household assets upon rural residents' self-reported physical and emotional well-being and disparities in health care among Vietnamese Americans in New Orleans and the impacts of Hurricane Katrina.